Analysis of the vaccination status of older adults - Pollyana Cristina dos Santos Ferreira; Nayara Gomes Nunes Oliveira; Darlene Mara dos Santos Tavares; Daniele Cristina Marques Machado (SciELO, 2021)
ABSTRACT Objective: To describe the sociodemographic characteristics, functional capacity and vaccination status of older adults, and to verify the factors associated with the incomplete vaccination status and the absence of the vaccination card. Method: Cross-sectional and analytical study conducted with older adults living in the city of Uberaba (MG). The following analyzes were carried out: descriptive, bivariate and multinomial logistic regression (p<0.05). Results: A total of 576 older adults participated. Most of them were women, in the 70-80 age group, with partner, low education and income, living with someone, independent in basic activities of daily living and with partial dependence on instrumental activities. The highest percentage was for older adults who had incomplete vaccination status, especially regarding the absence of immunization for Hepatitis B. Individual monthly income < 1 minimum wage (p=0.002) and single-person housing arrangement (p=0.010) were associated with the incomplete vaccination status, and the absence of the vaccination card, with the lowest level of education (p=0.039). Conclusion: Low income and education, as well as living alone, are factors associated with inadequate vaccination status among older adults in the community. The need for primary care nurses to develop strategies to increase vaccination coverage among older adults with these characteristics is emphasized.